Effects of Lattice Relaxation and Limiting Shear Stress of fcc Metals at High-Rate Deformation - Kamyshenko, V.V.; Kartuzov, V.V.; Shevchenko, V.I.; Gooch, W.A. (Проблемы прочности, 2002)
The results of calculations of the theoretical limiting shear stress for fcc metals Cu, Ni, Ag, Au, Pd, and Pt performed using “universal” empirical potentials of interatomic interactions of the embedded-atom type are presented. The effects of lattice relaxation are shown to play an important role in the formation of intermediate defect structures and lead to a considerable decrease in the theoretical yield point. Qualitative effects of the “anti-adiabatic” influence on the material ultimate strength under conditions of high-velocity loading are discussed. Наведено результати розрахунків теоретичної границі напруження зсуву для ГЦК-металів Cu, Ni, Ag, Au, Pd, Pt з використанням “універсальних” емпіричних потенціалів міжатомної взаємодії типу зануреного атома. Показано, що ефекти граткової релаксації відіграють важливу роль у формуванні проміжних дефектних структур і приводять до значного зменшення відповідних значень теоретичної границі текучості. Обговорюються ефекти “антиадіабатичного” впливу на граничну міцність матеріалу в умовах високошвидкісного навантаження. Представлены результаты расчетов теоретического предела сдвига для ГЦК-металлов Сu, Ni, Ag, Au, Pd, Pt с применением "универсальных” эмпирических потенциалов межатомного взаимодействия типа погруженного атома. Показано, что эффекты релаксации решетки играют важную роль в формировании промежуточних дефектных структур и приводят к значительному уменьшению соответствующих значений теоретического предела текучести. Обсуждаются эффекты “антиадиабатического” влияния на предельную прочность материала в условиях высокоскоростного нагружения.